The geopolitics of Russian gas pipelines in Europe. Between energy realism and energy liberalism. - Valle Padilla, Ana (Journal of the Spanish Institute for Strategic Studies, 2025)
The Russian invasion of Ukraine in 2022 intensified the ongoing conflict that began in 2014, prompting concerns about Europe’s energy security due to its dependence on Russian natural gas. Of the four pipelines that supply Russian gas to Europe, three were of particular concern: The Nord Stream, Yamal-Europe and the Ukrainian Transit System were the three principal pipelines through which Russian gas was transported to Germany, Poland and Ukraine, respectively. This study analyses Russia’s relations with these countries from the perspectives of realism and liberalism, examining how these theories interpret energy geopolitics. While Poland and Ukraine adopt a realist perspective, viewing Russian gas as a strategic vulnerability, Germany adheres to a liberal outlook, perceiving it as a commercial good that fosters stability. The results demonstrate the divergence in perceptions of natural gas, pipelines, and the relationship with Russia, as well as in national energy strategies. Despite these differences, the disruption of gas supplies did not occur, indicating the predominance of realism as an interpretative approach. This has led to the emergence of a new pipeline map and a new policy towards Russia.